Emerging Trends of Acquisition in Public Libraries of Pakistan: Challenges and Issues - Bashir, Faiza; Hanif Soroya, ,Saira; Soroya, M. Shahid; Khanum, Almas (Library Collections, Acquisitions, & Technical Services, 2015)
Acquiring material in public libraries is a core library activity to fulfill the unique needs of the reader's community. The present study aims to explore the trends of monograph acquisition in public libraries. The population consists of the four major public libraries of Lahore. A case study approach has been used to achieve the objectives of the study. Research is based on primarily the personal visits of the researcher to the acquisition departments of these libraries in order to collect data. Structured interviews were carried out with acquisition librarians to investigate the process of purchasing. The analysis of data reveals that a high ratio of Urdu language books has been purchased during the last decade, literature and religion being the major purchase area, whereas, art and architecture, pure sciences, and languages are the most neglected. The findings further revealed that the studied libraries have primarily been using traditional and informal techniques for acquiring material.
Keywords: Pakistan librarianship; acquisition trends; dept.ils; monograph acquisition; public libraries

Reading Trends of Youth in Pakistan: A Pilot Study - Soroya, Saira Hanif; Ameen, Kanwal (Pakistan Journal of Information Management and Libraries, 2016)
The present study, a part of researcher's Ph.D. project, aimed at exploring the reading trends of young Pakistani students (i.e., Generation Y: born during the 1980s and early 1990s, also known as internet generation), and the impact of digital media on their reading behavior. It was conducted as a pilot study on final year's master level students of the University of the Punjab. Quantitative research design, based on a survey was used. Convenient sampling technique was used to collect data from 50 students through questionnaire survey. It revealed that the students' reading behavior has been significantly changed during the last five years. Their overall reading time and digital reading time has been increased due to the availability of digital devices and digital reading material. The findings of this study are helpful in identifying the trends of reading behavior as well as in planning and designing library services with regard to the considering of the behavior of the students.
Keywords: dept.ils

Application of marketing approach in academic libraries: an exploratory study of Punjab University Libraries (PULs) - Soroya, Saira Hanif; Ameen, Kanwal (Pakistan Library & Information Science Journal, 2017)
Keywords: dept.ils

What do they want? Millennials and role of libraries in Pakistan - Soroya, Saira Hanif; Ameen, Kanwal (The Journal of Academic Librarianship, 2018)
The present study is aimed at determining the future role of libraries in Pakistan as perceived by the Millennials (people born during the 1980's and late 1990's) considering the current ongoing digital development. The quantitative research design, based on survey has been used for the study. The population consisted of students from large and medium sized general universities of Lahore, Pakistan. Stratified purposive sampling technique was carried out to select the pool of the subjects e. A self-constructed and validated instrument was used to collect data. The collected data was analyzed using SPSS (16.0). The results revealed that Millennials want future libraries to allow easy access to a wide range of reading material in both print and digital form. They want to be able to round the clock access to electronic and print resources.
Keywords: 21st century library users; Future role of libraries; Millennials; Pakistan; dept.ils

Users' Satisfaction as a Valid Measure for Information Resources: A Case of Public Libraries - Bashir, Faiza, Soroya ,Saira Hanif; and Khanum, Almas (Journal of Library Administration, 2018)
The mission of public libraries is to serve the unique needs of their local communities. Public library User's play a very vital role in the development of these libraries by suggesting or recommending additions to the collection. This study aims to evaluate the satisfaction of users with the quality and quantity of library collection. A self structured questionnaire based on open and close ended question was constructed. A purposive sample of one hundred users was selected. The data were qualitatively analyzed using a thematic approach. Positive opinion observed related to the library response towards the suggested titles. Almost half the population of respondents was satisfied with the availability of their suggested titles in library. Most of them were dissatisfied regarding the maintenance of equal collection of books and they are not encouraged by the library staff during the books suggestion process. It concludes that there is a need to evaluate the existing library collections.
Keywords: dept.ils; information quality; information resources; public libraries; user satisfaction

Do We Deliver What They Expect? Finding the Gap Between Users' Expected and Currently Received Library Services. - Ara, Mehvish; Soroya, Saira Hanif (Pakistan Library & Information Science Journal, 2018)
This research aims to assess tire service quality of public libraries of Lahore by evaluating the disparities between the users' expectation and currently received services. The survey method based on questionnaire was used. Four of the largest libraries in Lahore, in terms of services, collection and other facilities, were the population of the study. A sample of four hundred library users was selected with one hundred library users for each library based on convenience sampling. A modified LibQUAL+ tool was adopted to collect the data. The findings revealed that users have very high expectations regarding the accessibility of library's electronic resources from home or office, library website, printed material, availability of electronic information resource, modem equipment, tools that allow the users to find the material themselves, and provision of the information in an easy manner. The findings are helpful for public libraries' authorities to redcsign/upgradc the quality of library services, policies and procedures according to users' expectations and requirements.
Keywords: ACCESS control; INTERNET access for library users; LAHORE (Pakistan); LIBRARY public services; LIBRARY records; Libraries; Libraries and Archives; PUBLIC libraries; dept.ils

Mobilization in US Top University Libraries/美国高校图书馆移动服务现状调查与分析 - Yang, Q.; Liu, Y.Q. (Library & Information/图书与情报, 2015)
Keywords: dept.ils

The Latest Study of Workplace Bullying and Anti-Bullying in American Libraries/美国图书馆工作场所欺凌和反欺凌现状最新调研 - He, J; Wang, Y; Liu, Y. Q. (Library & Information/图书与情报, 2015)
Keywords: dept.ils

Anti-fraud schema system for identification and prevention of fraud behaviors in E-commerce services - Yang, Qinghong; Wei, Xing; Hu, Xiangquan; QuanLiu, Yan (Global Journal of Computer Science and Technology, 2016)
Keywords: dept.ils

Service Mode of Smart Recommendation Based on Knowledge Discovery/基于知识挖掘的图书馆智慧推荐服务模式 - Wang, Y.; Dong, X.; Liu, Y. Q. (Research on Library Science/图书馆学研究, 2018)

Multimedia Design & HCI in Libraries - Liu, Dr Yan Quan (2016)
The primary purpose of this book is to help students understand the principles of multimedia interface design to develop essential skills. The underlying philosophy of the approach of this text is that concepts are learned and remembered better when learned in a real work environment.
Keywords: dept.ils

Empirical Research for Information Professionals - Liu, Yan Quan (Information and library service studies, 2019)
A collection of empirical research published by Dr. yan Quan Liu and his reasearch teams in the field of information and library science for the 21st-century readers. - Back cover.
Keywords: Case studies; Library science; Research; Library science; dept.ils; faculty_collection

Information Science and Technology: An Introduction for Librarians (course Pack, 2nd Version) - Liu, Yan Quan (Create Space : Yan Quan Liu, 2018)
Keywords: Information science; Information technology; Information and Library Science; dept.ils; faculty_collection

Library Services for Mobile Users: A Library in the Palm of Your Hand - Liu, Yan Quan (CreateSpace, 2018)
This books is a print version of the online course ILS 440 Information Service Technology offered at Southern Connecticut State University. The course content includes the instructor's lecture notes, assignment instructions, assigned readings, discussions and coursework from students in the classes.
Keywords: Library applications; Public services (Libraries); Mobile communication systems; Technological innovations; dept.ils; faculty_collection

Transforming Library Service for the 21st Century User - Liu, Yan Quan (Createspace, 2018)
This book is a print version of the online course ILS508 User Services. The course content includes the instructor's lecture notes, assignment instructions, assigned readings, discussions an coursework from the students in the classes.
Keywords: Public services (Libraries); dept.ils; faculty_collection

Digital Libraries in Theory and Practices - Liu, Yan Quan (CreateSpace Independent Publishing Platform, 2016)
Keywords: Information storage and retrieval systems; dept.ils; faculty_collection

Library Services for Adults in the 21st Century - Okobi, Elsie A. Rogers Halliday (Libraries Unlimited, an imprint of ABC-CLIO, LLC, 2014)
"Develop the competencies needed to provide effective adult services in modern public libraries with this comprehensive guidebook"--
Keywords: Adult services in public libraries; United States; United States; Libraries and adult education; United States; Libraries and community; United States; Public services (Libraries); dept.ils; faculty_collection

Shu zi zhi shi bao ku zong lan: mei guo shu zi tu shu guan an li jing xi = Surfing the world of knowledge : analytical case studies of digital liberties [libraries] in the United States - 刘燕权; Liu, Yan Quan (Er shi yi shi ji tu shu guan xue cong shu. Di si ji, 2014)
Keywords: Digital libraries; United States; dept.ils; faculty_collection

Is data curation education at library and information science schools in North America adequate? - Harris-Pierce, R.L.; Liu, Y.Q. (New Library World, 2012)
Purpose: This study aims to present the results of a survey of library and information science (LIS) schools' websites used to determine if the number of data curation courses offered is adequate to address the needs of the so-called "data deluge". Many authors have identified a gap in the education of LIS students for data curation. Design/methodology/approach: This study surveyed the websites of LIS schools in North America to identify data curation courses. It reviewed and analyzed course descriptions, objectives and syllabi (when available) as well as compared course objectives, requirements, topics, assignments, and projects of the identified courses. Findings: Of the 52 LIS schools in North America's websites examined in this study, 16 institutions offered courses on data curation. The increase in the number of schools offering courses in data curation showed that LIS schools are responding to the demand for data curation professionals. More LIS schools need to add data curation to their curriculum. LIS schools currently offering data curation courses should continue to work together to determine the optimal course objectives and learning outcomes. Originality/value: Although there are several papers focused on particular data curation programs at a few universities, there are no papers that provide an overall view of the status of data curation education in higher education institutions today. This research will be of value and interest to LIS educators and professionals to determine if there is adequate education in place and to identify and evaluate the current state of data curation education. © Emerald Group Publishing Limited.
Keywords: Digital curation; Digital curation education; Digital librarianship; Digital libraries; Education of information and library science; Information and library school; Information management; dept.ils

Social indexing: A solution to the challenges of current information organization - Choi, Y. (Libr. Inf. Sci., 2014)
Purpose - This chapter aims to discuss the issues associated with social indexing as a solution to the challenges of current information organization systems by investigating the quality and efficacy of social indexing. Design/methodology/approach - The chapter focuses on the study which compared indexing similarity between two professional groups and also compared social tagging and professional indexing. The study employed the method of the modified vector-based Indexing Consistency Density (ICD) with three different similarity measures: cosine similarity, dot product similarity, and Euclidean distance metric. Findings - The investigation of social indexing in comparison of professional indexing demonstrates that social tags are more accurate descriptions of resources and reflection of more current terminology than controlled vocabulary. Through the characteristics of social tagging discussed in this chapter, we have a clearer understanding of the extent to which social indexing can be used to replace and improve upon professional indexing. Research limitations/implications - As investment in professionally developed web directories diminishes, it becomes even more critical to understand the characteristics of social tagging and to obtain benefit from it. In future research, the examination of subjective tags needs to be conducted. A survey or user study on tagging behavior also would help to extend understanding of social indexing practices. © 2013 by Emerald Group Publishing Limited.
Keywords: dept.ils

The Enlightenment of Pew Research Center's Information Management Practice on Academic Library Think Tank Services / 皮尤研究中心信息管理实践对学术图书馆智库服务的启示 - Liang, X.; Liu, Yan Quan (Library & Information, 2019)
Keywords: dept.ils; peer-reviewed; ⛔ No DOI found

Investigation and Research on the Application of Artificial Intelligence Technology in Library Service / 图书馆服务中人工智能技术应用的调查研究 - Yang, Z.; Wang, Y.; Liu, Yan Quan; Qu, Z. (Library/TU Shu Guan, 2019)
Keywords: dept.ils; ⛔ No DOI found

A complete assessment of tagging quality: A consolidated methodology - Choi, Yunseon (Association for Information Science and Technology, 2015)
This paper presents a methodological discussion of a study of tagging quality in subject indexing. The data analysis in the study was divided into 3 phases: analysis of indexing consistency, analysis of tagging effectiveness, and analysis of the semantic values of tags. To analyze indexing consistency, this study employed the vector space model-based indexing consistency measures. An analysis of tagging effectiveness with tagging exhaustivity and tag specificity was conducted to ameliorate the drawbacks of consistency analysis based on only the quantitative measures of vocabulary matching. To further investigate the semantic values of tags at various levels of specificity, a latent semantic analysis (LSA) was conducted. To test statistical significance for the relation between tag specificity and semantic quality, correlation analysis was conducted. This research demonstrates the potential of tags for web document indexing with a complete assessment of tagging quality and provides a basis for further study of the strengths and limitations of tagging.
Keywords: Consistency analysis; Consistency measures; Correlation analysis; Indexing (of information); Information retrieval; Latent Semantic Analysis; Organization of informations; Quality control; Quantitative measures; Semantics; Statistical significance; Subject indexing; Vector spaces; clinical trial; correlation analysis; data analysis; dept.ils; human; information retrieval; linguistics; model; organization of information; quantitative study; statistical significance; subject indexing

Analyzing tagging patterns by integrating visual analytics with the inferential test - Choi, Yunseon (Institute of Electrical and Electronics Engineers Inc., 2015)
Due to the large volume and complexity of data, exploring data using visual analytics has become more helpful to interpret and analyze it. The box plot is one of graphical ways and is the most common technique for presenting and summarizing statistics. In this paper, we focus on discussing the tagging patterns by integrating visualization assessment using the box plot with the Shapiro-Wilk test. © 2015 Author.
Keywords: Data analytics; Data visualization; Digital libraries; Large volumes; Shapiro-Wilk tests; Social tagging; Visual analytics; Visualization; data analytics; data visualization; dept.ils; social tagging

Content analysis of social tags generated by health consumers - Joo, Soohyung; Choi, Yunseon (Institute of Electrical and Electronics Engineers Inc., 2015)
This poster presents preliminary findings of user tag analysis in the domain of consumer health information. To obtain user terms, 36,205 tags from 38 consumer health information sites were collected from delicious.com. Content analysis was applied to identify the dimensions and types of the collected tags. The preliminary findings showed that user generated tags covers a variety of aspects of health information, ranging from general terms, subject terms, knowledge type, and to audience. General terms and subject terms were observed dominantly by showing 31.7% and 22.8% respectively. © 2015 Authors.
Keywords: Consumer health information; Content analysis; Digital libraries; Health; Health informations; Knowledge types; Qualitative analysis; Social Tags; Social networking (online); Social tagging; User-generated; consumer health information; dept.ils; qualitative analysis; social tagging

Effective techniques for the promotion of library services and resources - Yi, Zhixian (Information Research-an International Electronic Journal, 2016)
Introduction. This study examines how Australian academic librarians perceive techniques for promoting services and resources, and the factors affecting the perceptions regarding effectiveness of techniques used. Method. Data were collected from an online survey that was sent to 400 academic librarians in thirty-seven Australian universities. The response rate was 57.5%. Analysis. The qualitative data were analysed using content analysis. The collected quantitative and qualitative data were analysed using descriptive and inferential statistics (ordinal regressions). Results. Librarians used a variety of techniques to promote services and resources. Demographic variables, human capital variables and library variables were significant predictors of perceptions of the effective promotion techniques used. However, this study indicates that other independent variables such as number of different library professional positions and years involved in all library services made no difference. Conclusions. This study provides a better understanding of academic librarians' attitudes and views towards techniques for promoting services and resources. Librarians may use the results to reflect on the effectiveness of these techniques, to balance the weight of the factors' influences and to better understand various promotion techniques. This will enable them to promote library services and resources more effectively in the future.
Keywords: dept.ils; ⛔ No DOI found

Current market demand for core competencies of librarianship-a text mining study of american library association's advertisements from 2009 through 2014 - Yang, Qinghong; Zhang, Xingzhi; Du, Xiaoping; Bielefield, Arlene; Liu, Yan Quan (Applied Sciences-Basel, 2016)
As librarianship evolves, it is important to examine the changes that have taken place in professional requirements. To provide an understanding of the current market demand for core competencies of librarianship, this article conducts a semi-automatic methodology to analyze job advertisements (ads) posted on the American Library Association (ALA) Joblist from 2009 through 2014. There is evidence that the ability to solve unexpected complex problems and to provide superior customer service gained increasing importance for librarians during those years. The authors contend that the findings in this report question the status quo of core competencies of librarianship in the US job market.
Keywords: Competency; Job advertisement; Librarianship; Text mining; dept.ils; peer-reviewed

A library in the palm of your hand: mobile services in top 100 university libraries - Liu, Yan Quan; Briggs, Sarah (Information Technology and Libraries, 2015)
What is the current state of mobile services among academic libraries of the country's top 100 universities, and what are the best practices for librarians implementing mobile services at the university level? Through in-depth website visits and survey questionnaires, the authors studied each of the top 100 universities' libraries' experiences with mobile services. Results showed that all of these libraries offered at least one mobile service, and the majority offered multiple services. The most common mobile services offered were mobile sites, text messaging services, e-books, and mobile access to databases and the catalog. In addition, chat/IM services, social media accounts and apps were very popular. Survey responses also indicated a trend towards responsive design for websites so that patrons can access the library's full site on any mobile device. Respondents recommend that libraries considering offering mobile services begin as soon as possible as patron demand for these services is expected to increase.
Keywords: dept.ils; peer-reviewed

Web 2.0 applications' usage and trends in top US academic libraries - Boateng, Frank; Liu, Yan Quan (Library Hi Tech, 2014)
Purpose - This paper aims to explore Web 2.0 technologies usage and trends in the top 100 US academic libraries as exemplified through the academic library websites. Design/methodology/approach - The top 100 universities were selected from the US News & World Report's (USNWR) 2013 ranked list's top 100 of the best colleges in the USA. Content analysis was used in terms of quantitative approach. A checklist was developed as the main research instrument based on other checklists and questionnaires. Each of the selected university library websites was visited within a period of two weeks to explore implementation and usage of web tools, including SNS, blog, RSS, wikis, podcast/vodcast, and social bookmarking/tagging. Findings - All 100 academic libraries had a social media presence on Facebook and Twitter, making SNS the most widely applied Web 2.0 tool. The wild was the least applied Web 2.0 technology, with a 34 percent participation rate. Blog was the second most popular tool with a 99 percent participation rate, followed by RSS and IM/Chat with 97 percent and 91 percent respectively. The vodcast and podcast had 47 percent and 46 percent participation rates respectively, while social bookmarking/tagging were also used by 39 percent of the academic libraries. Research limitations/implications - This study is completely based on publicly available data regarding usage of Web 2.0 applications. Web 2.0 tools used on library intranets were not analyzed for this study. Outcomes suggest that academic libraries are increasingly using Web 2.0 applications to promote themselves, enhance library services, and highlight resources to patrons. Originality/value - This is the first research that draws an overall picture of the usage and trends of Web 2.0 applications in the top 100 US academic libraries. This study demonstrates some noticeable patterns regarding usage, trends, and adoption which are relevant to how Web 2.0 applications are perceived and used within academic libraries. The study provides academic libraries with helpful information to better meet their user needs by effectively applying Web 2.0. Additionally, library managers, librarians and other libraries may also find this research beneficial as they plan to deploy Web 2.0.
Keywords: Academic libraries; Library services; Technology usage; Web 2.0; dept.ils; peer-reviewed

From siloed data to linked data: Developing a social metadata repository - Choi, Yunseon (Wiley, 2014)
Although social data has been investigated and discussed regarding its impact on indexing and retrieval performance on the web, there has been little research conducted on storing or linking social data and identifying bibliographic relationships among social data for further use of social data. In this paper, we discuss our work in progress that aims to develop a social metadata repository which would be an important implication for making social data more valuable and reusable for searching and retrieval. We describe FRBR (Functional Requirements of Bibliographic Records) conceptual model's Entity-Relationship (ER) view on bibliographic relationships and demonstrate how social metadata are encoded in RDA (Resource Description and Access) and how the implicit bibliographic relationships of social data are explicitly represented as RDF (Resource Description Framework) triples (Subject - Predicates - Objects) with links to external sources. We believe that the shareable and linked metadata repository of social data is remarkably significant, not only because it supports the accessibility to related documents, but also because it is clarifying the implicit semantic relationships among social data.
Keywords: FRBR; Linked Data; Metadata; RDA; RDF; Social data; Social tags; dept.ils

The impact of senior citizens' use of online social networks on their cognitive function - Kim, Hak Joon; Kim, Joan (International Journal of Research Studies in Educational Technology, 2014)
Keywords: dept.ils

Reading from an LCD monitor versus paper: Teenagers’ reading performance - Kim, Hak Joon; Kim, Joan (International Journal of Research Studies in Educational Technology, 2013)
Keywords: dept.ils

Using dwell time as an implicit measure of usefulness in different task types - Liu, Chang; Liu, Jingjing; Belkin, Nicholas J; Cole, Michael J; Gwizdka, Jacek (Wiley, 2011)
In this study, we attempted to use dwell time on content pages as a predictor of document usefulness, and evaluated the prediction performance in different types of tasks. A user study was conducted to address this research problem. A total of 32 participants conducted searches associated with 4 different tasks, varying along several task type dimensions. In the study, participants were asked to save documents that were useful for the tasks during the searches. Participants' information-seeking activities were recorded. Using the logged dataset, we used the recursive partitioning method to identify the best threshold (cutoff point) of dwell time to predict which pages would be useful, i.e., be saved by the users. We examined the differences in the threshold and compared the prediction performance for each type of task. Our results indicate that the threshold should be developed according to the type of task users are working on. While the prediction performance using dwell time as the only indicator of document usefulness is acceptable for Factual tasks, it is not good for Intellectual tasks. Our results have implications on IR system design.
Keywords: Dwell time; Personalization; Task type; Usefulness prediction; dept.ils

Search task difficulty: the expected vs. the reflected - Liu, Jingjing; Belkin, Nicholas J (Association for Computing Machinery, 2011)
We report findings on how the user's perception of task difficulty changes before and after searching for information to solve tasks. We found that while in one type of task, the dependent task, this did not change, in another, the parallel task, it did. The findings have implications on designing systems that can provide assistance to users with their search and task solving strategies.
Keywords: Dependent tasks; Designing systems; Predicted difficulty; Reflected difficulty; Searching for informations; Task difficulty; Task type; User's perceptions; dept.ils

Understanding searchers' perception of task difficulty: Relationships with task type - Liu, Jingjing; Liu, Chang; Yuan, Xiaojun; Belkin, Nicholas J (Wiley, 2011)
We report findings that help us better understand the difficulty of tasks which involve information seeking, retrieving, gathering, and use. We examined the data gathered from two interactive information retrieval user studies on how users' perception of task difficulty changes before and after searching for information to solve tasks, and how the difficulty of tasks relates with users' background, previous experience with the tasks, and knowledge of the task topics, etc. The two studies employed carefully designed tasks with different types along several dimensions: task structure (subtasks being dependent upon or parallel with each other), task goal in quality (being specific or amorphous), and naming (being named or unnamed). It was found that while in some types of tasks, users' perceptions of task difficulty did not change before and after working on the tasks, in others, this did, either increasing or decreasing. Specifically, in the dependent-structured task, this did not change. In the parallel-structured or specific/named task, it decreased. In the amorphous/unnamed task, it increased. We also found that users' background factors do not normally correlate with their perceived task difficulty, or perceived difficulty change. In addition to helping understand the dynamic and complex nature of task difficulty, our findings have implications for system design that can provide assistance to users with their search and task solving strategies.
Keywords: Expected difficulty; Reflected difficulty; Task difficulty; Task type; dept.ils

Web 2.0 applications in top Chinese university libraries - Han, Zhiping; Liu, Yan Quan (Library Hi Tech, 2010)
Purpose - This paper aims to explore the status and construction pattern of Web 2.0 technologies employed in top Chinese university libraries, their functionalities and features. Design/methodology/approach - A combination of online survey and content analysis methodology is applied to a sample of 38 top Chinese university libraries' web sites. The Web 2.0 tools are categorized by generally accepted standards with some adjustment for library practices. Data were collected by accessing these university library web sites on two separate occasions during the period of February 10-20, 2009 by utilizing a checklist of 52 questions. Findings - More than two-thirds of the 38 top Chinese university libraries apply one or more kinds of Web 2.0 tools through the basic functions of their web sites. Among six types of tools, Catalog 2.0 and RSS are the most common, while IM, Blog, SNS and Wiki are less frequent. Research limitations/implications - Internal applications that are not publicly accessible contain hidden information that may not be gathered through content analysis since these links usually cannot be found on library web sites. It is difficult to get exact information as to the applications of Web 2.0 in these libraries without an interview method in combination to observation. Originality/value - This study provides an overall picture of Web 2.0 tools developed in top Chinese university libraries, allowing for future evaluation and planning. The implementation of Web 2.0 applications and their constructing pattern is not only indicative of the development of the Chinese digital libraries, but also to their development of digital libraries in the world at large.
Keywords: China; Digital libraries; University libraries; Worldwide web; dept.ils; peer-reviewed

Technical service outreach strategies for academic libraries - Toce, Jacqueline; Schofield, Cindy (Technical Services Quarterly, 2011)
The model of a library staff divided into technical and informational service divisions remains common-especially among academic libraries. The authors argue that in many ways it is now the technical services division that is best positioned to provide outreach services to a community-whether at the university or municipal level. Maintaining bibliographic access amid the changing information landscape hinges on a clear understanding of systems, metadata, and traditional organizational skills, all home grown in the back rooms of conventional libraries. The authors cite examples of library outreach that emanated from technical service departments and conclude that the sequestered staffs of the past must make themselves indispensible today by sharing their knowledge and talents, offering services to their communities that require their technical expertise, and advance the mission of the library organization. © Taylor & Francis Group, LLC.
Keywords: Academic libraries; Catalogers; Cooperative; Outreach; Service; Southern connecticut state university; Technical services; dept.ils; dept.lib

Public Libraries and the Opioid Crisis, Part 1: Context and Commitment - Real, Brian; Bogel, Gayle (Public Library Quarterly, 2019)
Public libraries have been significantly affected by the opioid crisis. The fact that patrons can enter libraries freely and do not need a reason to be there has resulted in overdoses occurring in many such buildings throughout the country. In response to this, library directors have developed plans of action that, in some cases, include training librarians to administer the opioid overdose reversal drug Naloxone. This present article – the first in a two-part study – is based on interviews with representatives from libraries that have been significantly affected by the opioid crisis. After describing these community circumstances, the authors analyze various ways that each library has prepared to respond to overdoses and other emergency situations.
Keywords: Narcan; Public libraries; dept.ils; opioid dependency; opioids; peer-reviewed

Public Libraries and the Opioid Crisis, Part 2: Community-Centered Responses - Real, Brian; Bogel, Gayle (Public Library Quarterly, 2019)
Numerous articles from major national newspapers have covered the fact that as the opioid crisis has become a pervasive problem in the United States, overdoses in public libraries have become a somewhat common occurrence. Many of these discussions center on librarians being trained to use the overdose reversal drug Naloxone, and that was the primary focus of the first part of this two-part study. However, this second article discusses what libraries are doing to mitigate the impacts of the crisis and help persons from vulnerable populations before matters escalate to become emergency situations. The authors document how libraries are attempting to educate their communities about the opioid crisis, ways they have partnered with community organizations to help opioid dependent persons, and how they have addressed various facilities and security concerns for their buildings.
Keywords: Public libraries; dept.ils; facilities management; opioids; peer-reviewed; security; vulnerable populations

Confronting librarianship and its function in the structure of white supremacy and the ethno state - Sierpe, Eino (Journal of Radical Librarianship, 2019)
Rising socio-cultural and political tensions have helped increase awareness about long-standing structures of violence and abuse, as we have seen in the development and tumultuous expansion of the #MeToo movement. However, other significant conditions of injustice and oppression continue without drawing attention. This seems to be the case with the library profession. Despite strong and persistent links to white supremacy and a well-established record excluding minorities from its ranks, the library profession has been remarkably successful in nurturing an unassailable public image of virtuous liberal benevolence and near mythical devotion to the highest ideals of freedom, individual rights, and democracy. Its unsurpassed ability in evading scrutiny or criticism of any serious consequence while maintaining a strong record of dedicated service to white power is all the more remarkable at a time where social media is used to amplify campaigns against injustices or organizations believed responsible for conditions of oppression. Although Critical Librarianship, or #CritLib, is beginning to question some of the doctrinal assumptions underlying the practice of librarianship, an examination of some of the mechanisms with which white supremacy has been able to build an entire system of racial protectionism as an occupational sector that intersects with areas of significant public interest is an important and timely research concern.
Keywords: dept.ils; peer-reviewed; ⛔ No DOI found

Are urban public libraries websites accessible to Americans with Disabilities? - Liu, Yan Quan; Bielefield, Arlene; McKay, Peter (Universal Access in the Information Society, 2019)
This paper examines to what extent the 129 members of the Urban Public Libraries Council meet the Section 508 standards for accessibility under the Rehabilitation Act, the minimum acceptable standard for accessibility under the Americans with Disabilities Act. Using an HTML evaluation tool, WAVE, the HTML coding of the libraries’ homepages was evaluated according to the Section 508 criteria for accessibility. After one-to-one deep examination to determine the accessibility of the library websites, the results tended to mirror other studies showing that most library websites have some coding deficiencies that limit the accessibility of the websites. Notably, only 7 of the 122 libraries that were surveyed had no Section 508 errors present with their homepages.
Keywords: ADA; Accessibility; Assistive technology; Compliance; Disability; HTML; Impairment; Libraries; Policy; Public libraries; Public library; Public policy; Section 508; Section508; Section 508; Universal usability; Urban libraries; Websites; dept.ils; peer-reviewed

An Analytical Study of Recommendation Systems in Chinese City Libraries / 城市图书馆馆藏资源推荐系统调查分析 - Guo, Q; Liu, Yan Quan; Wang, Y (Research on Library Science, 2019)
Keywords: dept.ils; peer-reviewed; ⛔ No DOI found

Differences, Complementarity and Convergence of University Library Mobile Service Platforms / 高校图书馆移动服务平台的差异、互补与融合 - Liu, Yan Quan; Zhao, F (Journal of the National Library of China, 2019)
Keywords: dept.ils; peer-reviewed; ⛔ No DOI found

The Model and Challenges of Volunteer Service Mechanism in American Urban Libraries / 美国城市图书馆志愿者服务机制模式及面临的挑战 - Ren, X; Liu, Yan Quan (Library & Information, 2019)
Keywords: dept.ils; peer-reviewed; ⛔ No DOI found

Effect of different areal precipitation estimation methods on the accuracy of a reservoir runoff inflow forecast model - Zhong, Wei; Li, Ruirui; Liu, Yan Quan; Xu, Jin (Institute of Physics Publishing, 2018)
Areal precipitation estimation directly affects the accuracy of reservoir runoff inflow forecasts and flood dispatching decision-making. Because of the heterogeneous spatial and temporal precipitation distributions in large basins, inadequate precipitation stations normally have a negative impact on forecast accuracy. Using the Panjia-kou reservoir runoff inflow forecast as the research subject, this paper adopts the Thiessen polygon block, square grid computing, and DEM (digital elevation model) methods to estimate average regional areal precipitation. Based on the estimation, a model for the Panjia-kou reservoir runoff forecast is developed. The results indicate that different areal precipitation estimation methods have significantly different effects on the accuracy of the reservoir runoff inflow forecast. When the average regional precipitation estimation from the DEM method is used as an input to the model, the simulation results are accurate and are much better than those from the other two average regional precipitation estimation methods.
Keywords: Air pollution; Areal precipitation; Decision making; Different effects; Digital elevation model; Forecast accuracy; Forecasting; Grid computing; Precipitation distribution; Precipitation estimation; Research subjects; Reservoirs (water); Runoff; Runoff forecast; Surveying; dept.ils

The provision of mobile services in US urban libraries - Guo, Ya Jun; Liu, Yan Quan; Bielefield, Arlene (Information Technology and Libraries, 2018)
To determine the present situation regarding services provided to mobile users in US urban libraries, the authors surveyed 138 Urban Libraries Council members utilizing a combination of mobile visits, content analysis, and librarian interviews. The results show that nearly 95% of these libraries have at least one mobile website, mobile catalog, or mobile app. The libraries actively applied new approaches to meet each local community’s remote-access needs via new technologies, including app download links, mobile reference services, scan ISBN, location navigation, and mobile printing. Mobile services that libraries provide today are timely, convenient, and universally applicable.
Keywords: dept.ils; human; mobile application; peer-reviewed; printing; publication; review

Bullying in the library workplace - Kim, Hak Joon; Geary, Carol Anne; Bielefield, Arlene (Library Leadership & Management, 2018)
The primary purposes of the study were to investigate how often bullying occurs in libraries and whether bullying policies exist in libraries. The first survey questionnaire was sent to library personnel in the six New England states through statewide email distribution lists. Altogether 571 library staff members completed the survey. The second survey questionnaire was sent to large public and academic libraries in New England to see if they have anti-bullying policies in the workplace. The results of the study clearly showed there were significant reports of workplace bullying in all kinds of libraries. Nonetheless, not many libraries have policies that deal with this workplace challenge.
Keywords: bullying; bullying polices; dept.ils; library policies; workplace bullying

Rural and small public libraries: challenges and opportunities - Real, Brian (Advances in Librarianship, Volume 43, 2018)
Keywords: Rural libraries; Small libraries; dept.ils

The hidden history of the American Film Institute: the cold war, arts policy, and American film preservation - Real, Brian (The Moving Image: The Journal of the Association of Moving Image Archivists, 2018)
The American Film Institute (AFI) presently does relatively little in terms of film preservation, but its founding in 1967 led to the growth of many of the mechanisms that define the motion picture preservation community today. As this article reveals, the AFI's success in promoting ongoing federal government support for motion picture preservation cannot be separated from the political context of the Cold War. The AFI's first director, George Stevens Jr., had previously been the head of the Motion Picture Service of the United States Information Agency (USIA). This work with a public diplomacy agency was essential to his vision for the design and structure of the AFI. Likewise, the AFI was founded as an independent nonprofit, but with the promise of significant ongoing funding support from the National Endowment for the Arts (NEA). While this arrangement worked well at first, a change in presidential administrations and design flaws in the AFI's support mechanisms led to it being unable to meet the expectations of the very film preservation community it helped to foster.
Keywords: dept.ils; peer-reviewed

Service mode of smart recommendation based on knowledge discovery - Wang, Y; Dong, X; Liu, Yan Quan (Research on Library Science, 2018)
Keywords: dept.ils; peer-reviewed; ⛔ No DOI found

Development path research on library smart service mode - Wang, Y; He, X; Liu, Yan Quan (Library Work and Study, 2018)
Keywords: dept.ils; ⛔ No DOI found

The present situation of mobile service in public libraries of China and the comparative analysis of public libraries in Eastern-Central-Western regions - Wang, Y; He, X; Liu, Yan Quan (Library, 2018)
Keywords: dept.ils; ⛔ No DOI found

An analytical review of sustainable development of American reading promotion policies - Dong, X; Liu, Yan Quan (Library, 2018)
Keywords: dept.ils; ⛔ No DOI found

Current situation and development trends of mobile services in the United States' urban libraries - Guo, Y; Liu, Yan Quan (Library and Information, 2018)
Keywords: dept.ils; ⛔ No DOI found

Forecasting of Chinese primary energy consumption in 2021 with GRU artificial neural network - Liu, Bingchun; Fu, Chuanchuan; Bielefield, Arlene; Liu, Yan Quan (Energies, 2017)
The forecasting of energy consumption in China is a key requirement for achieving national energy security and energy planning. In this study, multi-variable linear regression (MLR) and support vector regression (SVR) were utilized with a gated recurrent unit (GRU) artificial neural network of Chinese energy to establish a forecasting model. The derived model was validated through four economic variables; the gross domestic product (GDP), population, imports, and exports. The performance of various forecasting models was assessed via MAPE and RMSE, and three scenarios were configured based on different sources of variable data. In predicting Chinese energy consumption from 2015 to 2021, results from the established GRU model of the highest predictive accuracy showed that Chinese energy consumption would be likely to fluctuate from 2954.04 Mtoe to 5618.67 Mtoe in 2021.
Keywords: China; Energy consumption; Energy planning; Energy security; Energy utilization; Forecasting; Forecasting modeling; Forecasting scenarios; Gated recurrent unit; Gross domestic products; Multi-variable linear regression; Multivariable systems; Neural networks; Primary energy consumption; Support vector regression (SVR); dept.ils; energy consumption; energy planning; forecasting scenarios; gated recurrent unit

Equitable access: Information seeking behavior, information needs, and necessary library accommodations for transgender patrons - Drake, Aubri A.; Bielefield, Arlene (Library & Information Science Research, 2017)
This study highlights the unique accommodations integral to welcoming transgender library patrons. Research shows transgender people have unique needs which differ from lesbian, gay, bisexual, and queer (LGBQ) individuals, and experience substantial barriers to obtaining quality library service. Most studies in the past exploring the needs of lesbian, gay, bisexual, and transgender library users focused exclusively on LGBQ users. This study surveyed adult transgender individuals (n = 102) with an online questionnaire. The majority of participants were white, designated female at birth, and under 40 years old. Survey respondents needed libraries to make accommodations for them to feel safe (p ¡ 0.001). The top 5 accommodations needed were recent transgender literature, gender identity or expression as part of library nondiscrimination policy, gender neutral, single-stall bathrooms where a key did not need to be requested, recent LGBQ literature), and an established remote process for name change.
Keywords: dept.ils

Research on the current situation and countermeasures of the mobile information service in Chinese academic journals of library and information science - Zhao, F; Liu, Yan Quan; Wang, Y (Library and Information Service, 2017)
Keywords: dept.ils

The latest study of digital virtual reference service in Chinese top university libraries - He, X; Wang, Y; Liu, Yan Quan (Journal of Intelligence, 2017)
Keywords: dept.ils; ⛔ No DOI found

The latest study of reading promotion activities in American public libraries - He, X; Wang, Y; Liu, Yan Quan (Library and Information, 2017)
Keywords: dept.ils; ⛔ No DOI found

The election of Donald Trump to the presidency and the crisis of liberalism in librarianship - Sierpe, Eino (Journal of Radical Librarianship, 2017)
Keywords: dept.ils; peer-reviewed; ⛔ No DOI found